Analysis of different types of turnovers between winning and losing performances in men`s NCAA basketball - Hawkins, M.; Choi, H. (World Congress of Performance Analysis of Sport VIII, 2008)
A significant difference was found between winning and losing performances for different types of turnovers supporting current research that states that turnovers are not a valid predictor of match outcomes and that there is no specific type of turnover which can predict the outcome of a match as briefly mentioned in Curz and Tavares (1998). Significant differences were found between winning and tied and losing and tied performance for some types of turnovers, however due to the lack of data collected in this area they cannot be considered valid. In regards to analysis after the turnover, scoring occurred at a high percentage, nearly 50%, suggesting that a turnover results in effective scoring opportunities. However, over 20% of offences resulted in not achieving a shot or another turnover. Turnovers were seen to be exclusively committed in the offensive end of the court, largely due to the fact that full court defences were rarely seen so pressure and defence was not applied to attacking teams until they reached these areas of the court. Winning teams attempted less set up offences after a turnover than losing teams and attempted more fast breaks. Notably attempting more positive fast breaks where there are more offensive players than defensive players and less negative fast breaks where there are more defensive players than offensive, suggesting good decision making and potentially the reason why they were winning. In 5 out of the 7 matches analysed the winning team scored more points off turnovers committed by the opposing team. There is a large amount of scope for future research in the area of basketball and performance analysis and specifically performance indicators. The current study has raised several questions which would prompt further research such as comparison between fast breaks from turnovers and fast breaks from defensive rebounds to distinguish whether these factors make a difference and why it could make a difference. In terms of performance analysis, fast break decision making and decision making on a wider scale could be analysed, as many of the potential theories discussed were based around decision making, for example player`s ability to refrain from shooting in a negative fast break scenario and their ability to successfully convert positive fast break opportunities in winning and losing performances (Tavares & Gomes, 2003). Further research could also be conducted in other areas relating to performance indicators where there is currently minimal research in some areas such as assisted baskets, having said this further research into performance indicators must be approached with some caution, as Sporis et al. (2006) stated about the performance indicators in their own study the performance indicators are inadequate for explaining the complexities of the game suggesting that one indicator will not be constant in every game an research into performance analysis areas would be more appropriate.